MAIT cells are activated in acute Dengue virus infection and after in vitro Zika virus infection. - Dominic Paquin-Proulx; Vivian I Avelino-Silva; Bianca A N Santos; Nathália Silveira Barsotti; Fabiana Siroma; Jessica Fernandes Ramos; Adriana Coracini Tonacio; Alice Song; Alvino Maestri; Natalia Barros Cerqueira; Alvina Clara Felix; José Eduardo Levi; et al. (Public Library of Science (PLoS), 2018)
Dengue virus (DENV) and Zika virus (ZIKV) are members of the Flaviviridae and are predominantly transmitted via mosquito bites. Both viruses are responsible for a growing number of infections in tropical and subtropical regions. DENV infection can cause lethargy with severe morbidity and dengue shock syndrome leading to death in some cases. ZIKV is now linked with Guillain-Barré syndrome and fetal malformations including microcephaly and developmental disorders (congenital Zika syndrome). The protective and pathogenic roles played by the immune response in these infections is unknown. Mucosal-associated invariant T (MAIT) cells are a population of innate T cells with potent anti-bacterial activity. MAIT cells have also been postulated to play a role in the immune response to viral infections. In this study, we evaluated MAIT cell frequency, phenotype, and function in samples from subjects with acute and convalescent DENV infection. We found that in acute DENV infection, MAIT cells had elevated co-expression of the activation markers CD38 and HLA-DR and had a poor IFNγ response following bacterial stimulation. Furthermore, we found that MAIT cells can produce IFNγ in response to in vitro infection with ZIKV. This MAIT cell response was independent of MR1, but dependent on IL-12 and IL-18. Our results suggest that MAIT cells may play an important role in the immune response to Flavivirus infections.